THE EFFECTIVENESS OF SHORT ANIMATION VIDEO ON STUDENTS’ VOCABUARY MASTERY - Wa Ode Fifin Dwi Agustin; La Dunifa; Nining Syafitri (English Education Journal, 2022)
The problem in this research was whether there was a significant difference on students’ vocabulary mastery before and after the application of short animation video? The objective of the research was to determine the effectiveness of using short animation video on students’ vocabulary mastery. This research uses a pre-experimental method. The subject of the research consisted of 26 students of class VII at SMPN 7 Baubau. This research was one group pretest-posttest. The procedure of the research consisted of three steps. They were pretest, treatment, and posttest. The data was collected by using the test which was analyzed by quantitative analysis. The research outcome indicated that: 1) the mean value of the pretest was 44.12 and the mean score of the posttest was 68.85. 2) from the hypothesis result by using the t-test, obtained tcount was 4.564, and the sig. (2-tailed) was 0.000 smaller than 0.05, so that, Ha is accepted and Ho is rejected. it meant that there was a significant difference on students' vocabulary mastery before and after the application of the short animation video. Therefore, teaching vocabulary in SMPN 7 Baubau by using short animation video was effective.